Characterization of Hot Workability for a Near Alpha Titanium Alloy by Integrating Processing Maps and Constitutive Relationship. Issue 7 (12th March 2019) - Zhou, Dadi; Zeng, Weidong; Xu, Jianwei; Chen, Wei; Wang, Simin
Abstract : Hot workability of near‐alpha titanium alloy Ti–6Al–3Nb–2Zr–1Mo with an initial duplex microstructure is evaluated through isothermal compressions in lower α + β phase field, upper α + β phase field, and β phase field. It is noteworthy that flow stress increases with increasing strain rates and decreasing temperatures. Based on Dynamic Material Model and Prasad's instability criterion, processing maps are established and subdivided into six characterization regions to ascertain deformation mechanisms connected with microstructure. The results show that super‐plasticity deformation (SPD) and dynamic recrystallization (DRX) of β phase can be achieved in the area with high power dissipation efficiency in α + β phase field and β phase field, thus making them being the optimum hot working domains. Besides, DRX of lamellar α, dynamic recovery (DRV) of equiaxed primary α ( αp ) as well as DRV of β phase occur in the remaining safe domains with increasing temperature. The microstructure in instability domains, where hot deformation should be kept away, is characterized by flow localization. Arrhenius‐type constitutive model incorporated with strain compensations is selected to describe the high‐temperature flow behavior of the test Ti‐alloy. The introduction of three detailed divisions with temperature ranges gives an accurate calculation for apparent activation energy. Abstract : 1. It is demonstrated that SPD and DRX of β phase achieved in the area with high η value in α+β and β phase field. 2. It is confirmed that DRX of lamellar α, DRV of equiaxed αp as well as DRV of β phase occurred in the remaining safe domains with increasing temperature.